Cognitive Phenomenology of Religious Experience in Religious Narratives, Dreams, and Nightmares. (December 2015) - McNamara, Patrick; Minsky, April; Pae, Victoria; Gusev, Alina
McNamara (2009) hypothesized that a 4-step sequential decentering process (diminished agency, liminality, effort, and success) characterized the phenomenology of religious and spiritual experiences (RSES) and was rooted in dreams and nightmares. We content analyzed 50 RSES, 50 dreams, and 50 nightmares for presence and ordering of elements of the decentering process. Thirty-six percent of RSES, 48% of dreams, and 44% of nightmares had all four decentering elements. The sense of success occurred most frequently in RSES (11% of all decentering instances) and least frequently in nightmares (5%). Conversely, diminishment of agency occurred least often in RSES (7% of all decentering instances) and most often in nightmares (10%). For RSES 66% of instances of effort occurred, as hypothesized, after liminality and diminishment. We conclude that an orderly 4-step decentering process is reliably detectable in many, but not all, RSES, and that randomly ordered decentering elements occur abundantly in dreams and nightmares.